FINDING THE RATE OF INTEREST. - Stelson, Hugh E.; Snyder, Ralph W. (The Accounting Review, 1953)
Abstract The article highlights that in problems in the mathematics of finance where it may be desired to find an unknown rate of interest, a uniformity of approach to approximation formulas of considerable accuracy can be achieved for the three fundamental functions and their inverse functions, and also for the bond function, by means of the concept of the total interest growth over the term of the investment, or indebtedness. The article presents various methods to calculate the rate of interest. The total interest, present value of annuity, amount of annuity is first calculated. By means of these relations, the article is able to make substitutions in the usual formulas, obtaining what may be termed indirect formulas, which give rise to series that converge more rapidly than the series obtained by expansion of the original formulas. The new formulas are used as the bases for approximations to the interest rate. The article also presents a table to show the formulas for the calculation of present value of annuity or installment payment problems.